"JURISPRUDENTIAL MASSAGE": Legal Fictions, Sectarian Citizenship, and the Epistemics of Dissent in Post‐socialist China. (25th November 2020) - PIA, ANDREA E.
ABSTRACT: While China leads the global race to high‐tech surveillance, a homegrown low‐tech institution of dissent management is currently experiencing a surprising revival: dispute mediation. Drawing on Confucian and socialist practices of justice, Yunnanese dispute mediators are today considerably innovating the jurisprudential techniques that frame the composition of conflict and the meaning of state laws in dispute settings. Jurisprudential massage is the emic term given to one such technique. Here I show how this technique stands for the deployment of therapeutic analogies and legal fictions with the aim of reorienting the political sensibilities of disputants toward a neo‐paternalistic form of citizenship. Contributing to the anthropology of law and resistance, this article shows how civil dissent cannot only be physically quenched through state coercion and silenced by pervasive surveillance or tactical buyouts but can also be ushered off the political stage by a selective redrawing of the epistemic foundation of legality. Abstract :